2022
DOI: 10.1186/s12902-022-01079-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a patient education programme for children, adolescents, and young adults with differences of sex development (DSD) and their parents: study protocol of Empower-DSD

Abstract: Background Differences in sexual development (DSD) are rare diseases, which affect the chromosomal, anatomical or gonadal sex differentiation. Although patient education is recommended as essential in a holistic care approach, standardised programmes are still lacking. The present protocol describes the aims, study design and methods of the Empower-DSD project, which developed an age-adapted multidisciplinary education programme to improve the diagnosis-specific knowledge, skills and empowermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Disease-specific education and skill-building interventions strengthen knowledge and self-management skills for patients with chronic endocrine disorders, such as T1D [13,14], Klinefelter syndrome [15 ▪ ,16] and Turner syndrome [16]. These interventions can be integrated into transition clinics, focus groups, workshops, classes and camps, and may be led by clinicians, trained educators, social workers or psychologists.…”
Section: The Stages Of Healthcare Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease-specific education and skill-building interventions strengthen knowledge and self-management skills for patients with chronic endocrine disorders, such as T1D [13,14], Klinefelter syndrome [15 ▪ ,16] and Turner syndrome [16]. These interventions can be integrated into transition clinics, focus groups, workshops, classes and camps, and may be led by clinicians, trained educators, social workers or psychologists.…”
Section: The Stages Of Healthcare Transitionmentioning
confidence: 99%
“…Patel et al [39] reported that increased patient age, higher level of education, more life skills, and greater Turner syndrome knowledge, confidence and social/emotional skills were associated with higher transition readiness. Education programmes have been designed to improve Turner syndrome-specific knowledge, skills and empowerment of patients and their parents [16]. Transition tools specific to Turner syndrome are noted in Table 1.…”
Section: Turner Syndromementioning
confidence: 99%
“…To date, it collected information from 1,040 persons with DSD conditions in six countries (Germany, France, the Netherlands, Poland, Sweden, and the UK). Another example is the Empower-DSD project, which is a prospective, longitudinal, and noncontrolled multicenter study led in Germany with the main aim of developing, implementing, and evaluating an age-appropriate educational program for 700 children and young people with DSD ( 3 ).…”
Section: Introductionmentioning
confidence: 99%